Political Economy of Oil-Revenue Sharing in a Developing Country : Illustrations from Nigeria - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2003)
Control over natural resource revenues is a contentious, politically divisive issue in most developing countries-especially for oil production. A typical policy response of the center in such cases has been to introduce revenue sharing arrangements. Such measures have generally not assuaged the aspirations of the oil-producing regions and have exposed them to volatility in their revenue flows that they are generally unable to cope with. An alternative is to assign more stable revenue bases to the regional administrations, together with a general-purpose transfer system that incorporates a floor. This acts as an insurance mechanism for the regional administrations and facilitates the stable provision of public services in the oil-production regions, as well as the possibility of redistribution. We use the recent history of oil-revenue sharing in Nigeria to illustrate the propositions.